THE EFFECTIVENESS OF EXERCISE KEGEL ON THE HEALING PROCESS OF EFFICIOTOMIC INFLAMATION AND PROLIFERATION PHASE ON POSTPARTUM MOTHER - Yuliani Budiyarti (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2019)
Background: One of the actions that can be taken to accelerate labor and widen the birth canal is episiotomy. If the post episiotomy wound does not receive treatment measures such as exercice, it can cause negative effects such as the length of time the wound heals is at high risk of infection. The purpose of this study is to prove the effectiveness of Kegel Exercise on the healing process of episiotomy wounds in the inflammatory and proliferation phases of post partum mothers. Method: This type of quantitative research with a quasi experimental design of posttest only non-equivalent control group. The research sample of post partum mothers with episiotomy as many as 40 people were divided into two groups: 20 mothers of the intervention group and 20 mothers of the control group, using purposive sampling techniques and Mann Whitney analysis test. Results: p value 0,000 ≤ value α = 0.05 so that Kegel Exercise is effective in the healing process of episiotomy wounds in the inflammatory and proliferative phases in post partum mothers. Conclusion: Kegel exercise can be used as an alternative action that is easy and safe to accelerate the healing process of episiotomy wounds in post partum mothers.